2013
DOI: 10.2340/16501977-1098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lower extremity functional electrical stimulation pulsed isometric contractions on arm cycling peak oxygen uptake in spinal cord injured individuals

Abstract: Objective: To compare peak oxygen uptake (VO 2peak ) between: (i) functional electrical stimulation lower extremity pulsed isometric muscle contractions combined with arm cycling (FES iso hybrid), (ii) functional electrical stimulation cycling combined with arm cycling (FES hybrid cycling), and (iii) arm cycling exercise (ACE) in individuals with spinal cord injury with level of injury above and below T6. Design: Cross-over repeated measures design. Methods/participants: Individuals with spinal cord injury (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Moreover, arms-only exercise in SCI can be limited by the inability to vasconstrict in the nonactive legs (31), whereas hybrid FES exercise obviates the need for this vasoconstriction (30). The normally ‘wasted’ blood flow to the legs serves a purpose to allow for increased oxygen consumption (6,7,29). In fact, regular FES training can result in a reduction in the normally strong inverse relationship between injury level and peak aerobic capacity (28).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, arms-only exercise in SCI can be limited by the inability to vasconstrict in the nonactive legs (31), whereas hybrid FES exercise obviates the need for this vasoconstriction (30). The normally ‘wasted’ blood flow to the legs serves a purpose to allow for increased oxygen consumption (6,7,29). In fact, regular FES training can result in a reduction in the normally strong inverse relationship between injury level and peak aerobic capacity (28).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that rapid recovery of the muscle strength in the injured ankle to the level of intact limb in the first year after treatment is not only the result of cross impact exercises for the muscles of intact limb [15], but is also due to development of post injury muscle hypertrophy. Hypertrophy develops under the influence of a lower muscle sensitivity threshold to the somatic vegetative signals during functional loading of the recovering limb [12].…”
Section: Discussionmentioning
confidence: 91%
“…Given that some individuals with incomplete SCI may retain the capacity to voluntarily activate muscles in the lower limbs, we anticipated greater muscle activation with the arm-leg exercise equipment than with arm-only (which would translate into increased VO 2 ). Whereas previous work has shown greater metabolic demand for hybrid versus arms-or legs-only exercise in this population, [8][9][10]17 all of these studies have utilised FES. Therefore, it appears that in order for there to be any significant metabolic advantage to hybrid exercise, the equipment must involve electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies that have attempted to compare exercise modes using these variables; the majority have utilised functional electrical stimulated (FES) exercise and have reported greater oxygen requirements for hybrid FES rowing compared with arm-only rowing 8 and for FES hybrid cycling versus arm cycling. 9 Further, a study by Hasnan et al 10 revealed that both arm-only exercise and hybrid FES arm-leg exercise elicited a higher VO 2 and HR response compared with FES leg exercise alone. Accordingly, electrically stimulating paralysed muscle may provide some metabolic advantage during exercise, although this equipment is relatively expensive and resource intensive compared with basic aerobic and resistance equipment.…”
Section: Introductionmentioning
confidence: 98%